Self-induced growth of GaN nanorod assembly on flexible niobium metal foil using laser molecular beam epitaxy. (November 2020) - Ramesh, Ch.; Tyagi, P.; Gautam, S.; Mauraya, A.K.; Ojha, S.; Gupta, G.; Kumar, M. Senthil; Kushvaha, S.S.
Abstract: Self-induced GaN nanorod (NR) growth on flexible niobium (Nb) metal foil has been reported using laser assisted molecular beam epitaxy (LMBE) technique. The role of growth temperature (600, 650 and 700 °C), laser repetition rate (10–30 Hz) and Nb foil pre-nitridation condition on the formation and properties of GaN NRs have been studied systematically. The dense (~2.42 × 10 9  cm −2 ) GaN NRs were grown on pre-nitridated Nb metal foil at growth temperature of 700 °C with length and diameter of ~550–640 nm and ~60–130 nm, respectively. The low growth temperature of 650 °C or the high laser repetition rate of 30 Hz increases the radial growth rate of GaN NRs on Nb foil which results the coalescence of NRs. The size and density of GaN NRs on Nb metal foil could be controlled with tuning of LMBE growth parameters. The GaN NRs obtained on bare and nitridated Nb foil have excellent optical properties with an intense near band emission peak position at ~3.40 eV and a narrow linewidth of 90–100 meV. The controlled growth of GaN NRs with excellent optical quality on Nb foil offers the possibility of realization of futuristic high efficient flexible III-nitride nanostructure-based optoelectronic devices. Highlights: Laser molecular beam epitaxy growth of GaN nanorods on flexible Nb metal foil. Role of growth temperature from 600 to 700 °C on morphology of GaN nanostructures. C-axis growth of GaN nanorods on flexible Nb foil at growth temperature of 700 °C. Wet etching showed the N-polar growth of GaN nanorods on Nb foil. High optical quality of GaN nanorods grown on bare and nitridated Nb foil.